On Fractional Order Hybrid Differential Equations - Mohamed A. E. Herzallah; Dumitru Baleanu (Abstract and Applied Analysis)
We develop the theory of fractional hybrid differential equations with linear and nonlinear perturbations involving the Caputo fractional derivative of order 0<α<1. Using some fixed point theorems we prove the existence of mild solutions for two types of hybrid equations. Examples are given to illustrate the obtained results.